GAMBARAN FAKTOR-FAKTOR YANG TERKAIT DENGAN KEANEKARAGAMAN HAMA GUDANG PADA TEPUNG TERIGU DI PASAR TRADISIONAL KOTA SEMARANG - Eka Indri Astuti; Sri Yuliawati; Rully Rahadian (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
Wheat flour is very vulnerable pests if stored in warehouses for long periods, especially in traditional markets. The purpose of research to describe of factors related to diversity warehouse pests of wheat flour in tradisional market town of Semarang. This research is descriptive, using survey method with cross sectional approach. The sample in this research was flour trader sold in stall and los located at 6 UPTD Traditional Market Town of Semarang who met the inclusion criteria. Data analysis using univariate analysis. The results showed there are six species found that Sitophilusoryzae, Triboliumcastaneum, Lasiodermaserricorne, StegobiumPaniceum, Carpophilushemipterus and Silvanus sp with the species most commonly found are Triboliumcastaneum (91,67%). UPTD Jatingaleh have categories circumstances worst wheat flour products (77,8%). Sanitary place to do business, there are 4 UPTD with a percentage of 100% classified as bad in the UPTD Jatingaleh, Karangayu, Pedurungan and Karimata.